Salt Stress Alleviation in Field Crops Through Nutritional Supplementation of Silicon - Ali, Anser; M.A., Shahzad; Hussain, Safdar; Iqbal, Javaid; Bukhsh, M. Ahmad Alias Haji A.; Sarwar, Muhammad (Pakistan Journal of Nutrition, 2012)
Soil salinity is a huge problem negatively affecting physiological and metabolic processes in plant life, ultimately diminishing growth and yield. Salts taken up by the plants influence the plant growth by inducing adverse effects on different physiological and biochemical processes, including turgor, photosynthesis and enzymatic activities. Mechanisms responsible for reduction in plant growth under salt stress are: (1) Osmotic stress, (2) Specific ion toxicity, (3) Nutritional imbalance and (4) Oxidative stress. Different approaches such as introduction of new genes into genotypes responsible for salt tolerance, screening of large international collections and conduct of field trials on selected genotypes, conventional and non-conventional breeding methods and adequate regulation of mineral nutrients have been employed to enhance salinity tolerance in plants. Saline agriculture and exogenous application of mineral elements including Si has been professed as cost effective approach to ameliorate the salt stress in cereal crops like wheat. Si is categorized as a beneficial element in plant biology. It is unquestionably an important requirement for the normal growth of many plants and must be called as “Quasi essential”. Si amendment also plays a pivotal role to enhance chlorophyll content, stomatal conductance, photosynthesis and rigidity of plants under stressful conditions. There are different mechanisms by which Si mediates salinity tolerance in plants. It maintains the plant water status under saline conditions. It reduces uptake of Na+ by improving K+: Na+ and also alleviates the toxicity of other heavy metals. It application helps to improve the defensive system of the plants by producing anti-oxidants which in turn detoxify reactive oxygen species. Morphological and physiological improvements in plants were observed due to Si deposition within plant body under salt stress conditions. Silicon improves growth and dry matter production under salt stress conditions. Its application also enhances the crop performance against biotic stress. It is, therefore, suggested that supplemental application of Si must be included in salt stress alleviation management techniques.